2020
DOI: 10.3389/fncel.2020.00247
|View full text |Cite
|
Sign up to set email alerts
|

PHF-Core Tau as the Potential Initiating Event for Tau Pathology in Alzheimer’s Disease

Abstract: Worldwide, around 50 million people have dementia. Alzheimer’s disease (AD) is the most common type of dementia and one of the major causes of disability and dependency among the elderly worldwide. Clinically, AD is characterized by impaired memory accompanied by other deficiencies in the cognitive domain. Neuritic plaques (NPs) and neurofibrillary tangles (NFTs) are histopathological lesions that define brains with AD. NFTs consist of abundant intracellular paired helical filaments (PHFs) whose main constitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 91 publications
1
11
0
Order By: Relevance
“…Neurodegenerative diseases offer a broad spectrum of neurological diseases. Most often they are caused by the accumulation of intraneuronal bundles of hyperphosphorylated tau protein, in the form of neurofibrillary tangles, neuritic plaques and dystrophic neurites [96], as well as extracellular aggregates of beta-amyloid plaques, all characterizing Alzheimer's disease (AD). However, the link between amyloid deposits and neurofibrillary tangles is not yet clear, despite at least three decades of research devoted to finding the trigger factors of these proteinopathies and to understanding the timeline of molecular and biochemical events leading to their pathology [97].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Neurodegenerative diseases offer a broad spectrum of neurological diseases. Most often they are caused by the accumulation of intraneuronal bundles of hyperphosphorylated tau protein, in the form of neurofibrillary tangles, neuritic plaques and dystrophic neurites [96], as well as extracellular aggregates of beta-amyloid plaques, all characterizing Alzheimer's disease (AD). However, the link between amyloid deposits and neurofibrillary tangles is not yet clear, despite at least three decades of research devoted to finding the trigger factors of these proteinopathies and to understanding the timeline of molecular and biochemical events leading to their pathology [97].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…In AD, eNFTs are composed primarily of the protease-resistant PHF-core comprised of a 92-95 amino acid fragment culminating at Glu391 and recognized by the 423 antibody. Truncation at Asp421, generated by caspase-3, has been associated with the early molecular stages of neurodegeneration in AD [20]. Truncation at Asp421 and Glu391 favor the polymerization of tau protein into highly insoluble filaments.…”
Section: Extracellular Neurofibrillary Tanglesmentioning
confidence: 99%
“…It is the minimal paired helical filament core fragment (PHF-core) [30][31][32] with a truncation at Glu391 [33], and which is recognized by the antibody 423 [34]. Recent studies have suggested that the PHF-core is an early initiating event of AD pathology [20]. It has been shown that the C-terminal region of tau is very susceptible to proteolysis [29,35].…”
Section: Molecular Processing Of the Tau Proteinmentioning
confidence: 99%
“…In general, the results showed that the interactions of the P-Ser262 complex were very similar to the control, but they increased significantly with increasing the number of phosphorylated sites to three. Indeed, as NC and NHB increase in P-Ser262, 285, 289 complex, the possibility of stable dimers increases, which is the first step in PHF formation ( Luna-Viramontes et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%